Testing the utility of three social-cognitive models for predicting objective and self-report physical activity in adults with type 2 diabetes - Plotnikoff, Ronald C.; Lubans, David R.; Penfold, Chris M.; Courneya, Kerry S. (British journal of health psychology, 2014)
Objective Theory‐based interventions to promote physical activity (PA) are more effective than atheoretical approaches; however, the comparative utility of theoretical models is rarely tested in longitudinal designs with multiple time points. Further, there is limited research that has simultaneously tested social‐cognitive models with self‐report and objective PA measures. The primary aim of this study was to test the predictive ability of three theoretical models (social cognitive theory, theory of planned behaviour, and protection motivation theory) in explaining PA behaviour. Methods Participants were adults with type 2 diabetes (n = 287, 53.8% males, mean age = 61.6 ± 11.8 years). Theoretical constructs across the three theories were tested to prospectively predict PA behaviour (objective and self‐report) across three 6‐month time intervals (baseline–6, 6–12, 12–18 months) using structural equation modelling. PA outcomes were steps/3 days (objective) and minutes of MET‐weighted PA/week (self‐report). Results The mean proportion of variance in PA explained by these models was 6.5% for objective PA and 8.8% for self‐report PA. Direct pathways to PA outcomes were stronger for self‐report compared with objective PA. Conclusions These theories explained a small proportion of the variance in longitudinal PA studies. Theory development to guide interventions for increasing and maintaining PA in adults with type 2 diabetes requires further research with objective measures. Theory integration across social‐cognitive models and the inclusion of ecological levels are recommended to further explain PA behaviour change in this population. Statement of contribution What is already known on this subject? Social‐cognitive theories are able to explain partial variance for physical activity (PA) behaviour. What does this study add? The testing of three theories in a longitudinal design over 3, 6‐month time intervals. The parallel use and comparison of both objective and self‐report PA measures in testing these theories.